Enhancing Learning Discipline Through Self-Management and Modelling Techniques: A Study of Students at Cipasung Tasikmalaya Islamic Middle School - Rinto Gunawan; Muhammad Nur Wangid (AL-ISHLAH: Jurnal Pendidikan, 2025)
Learning discipline is a critical factor influencing academic success, particularly in socio-economically diverse rural settings. At Cipasung Islamic Middle School in Tasikmalaya, West Java, many students come from low-income families, and local socio-cultural conditions may hinder the development of effective learning behaviors. This study investigates the effectiveness of self-management and modeling techniques in improving students’ learning discipline. A quasi-experimental design with nonequivalent control groups was employed. The experimental group received counseling using self-management techniques, while the control group received counseling through modeling techniques. Both groups completed a pretest, underwent their respective interventions, and took a posttest to measure changes in discipline. Analysis revealed that the self-management group demonstrated a significantly higher increase in learning discipline compared to the modeling group. Statistical tests confirmed a notable difference in the effectiveness of the two techniques. Self-management techniques, which emphasize goal-setting, self-monitoring, and self-evaluation, proved more effective in fostering consistent learning discipline. These techniques appear to enhance students’ independence and responsibility for their academic behavior. Self-management-based counseling interventions show strong potential in improving student discipline, particularly in under-resourced educational settings. Schools without structured discipline programs are encouraged to adopt such methods to support student development.